HOW MUCH FOR A LEGAL INTERN? INTERNSHIPS AT LAW OFFICES IN SERBIA - Đorđević, Mila; Vlajić, Milica (Pravni zapisi, 2023)
The aim of this paper is to examine the position of legal interns in Serbia. The first part of the paper provides the theoretical framework for the research, as well as an overview of the normative position of legal interns, whereas the second part presents the methodological framework of the research and analysis of the data collected from 517 respondents. The results of the study confirm the hypothesis that current socio-economic changes have led to the transmission of stratification within the legal profession to the position of legal interns. Additionally, the data provide valuable insights into the experiences and challenges faced by legal interns, which have implications for the review of legal regulations governing their rights and obligations.
Keywords: legal profession; legal interns; young people; labour market